Horizontal Accuracy Assessment of High Resolution Satellite Imagery forMapping Purposes - Alwan, Imzahim (Iraqi Journal of Science, 2024)
The New generation remote sensing satellites that are being designed to imageobjects on the Earth’s surface with a resolution of one meter and less. It is believedthat such high resolution satellite imaging systems will lead to a paradigm change inmapping science, considering the high resolution, wide spectral range, and stereomapping capabilities. This will be the first time that users around the world will beable to use satellite imagery to map products on the plane ground at a sub-meterlevel. This paper presents the results of an assessment of the horizontal accuracy ofthe new generation of high-resolution satellite imagery WV02 one of the DigitalGlobe productions for mapping purposes. Based on Evaluation of the planimetricaccuracies of Worldview02 Ortho Ready Standard image acquired under a SpaceImaging/NASA Data was found the value range to be (1.1 m and 1.55 m) CE90 attest site. The experimental results are very encouraging. It is demonstrated that withtwo or more GCPs, the sub-meter satellite imagery will have a potential to generatemapping products with a map scale of 1:4,000, which is sufficient for many GISapplications.